Réponses

  • Utilisateur Brainly
2014-09-14T12:44:00+02:00
(5x - 8)(x - 3) - (x + 1)(x - 3) = 0
(x - 3)(5x - 8 - x - 1) = 0
(x - 3)(4x - 9) = 0
Un produit est nul si un de ses facteur est nul.

x - 3 = 0
x = 3

ou 

4x - 9 = 0
4x = 9
x = 9/4

S= {9/4 ; 3}
Pourquoi est tu passer de +1 a -1 ? (dans la deuxieme ligne)
Meilleure réponse !
2014-09-14T12:50:59+02:00
(5x - 8) (x - 3) - (x + 1) (x - 3) = 0
(x - 3) (5x - 8 - x - 1) = 0
(x - 3) (5x - x - 8 - 1) = 0
(x - 3) (4x - 9) = 0
Un produit est nul si un de ses facteur est nul.

x - 3 = 0        ou                    4x - 9 = 0
x = 3                                      4x = 9
                                             x = 9/4
                                             x = 2,25




S= {9/4 ; 3}

Pourquoi est tu passer de +1 a -1 ? (dans la deuxieme ligne)